Political Deliberation, Interest Conflict, and the Common Knowledge Effect - C. Daniel Myers (Journal of Deliberative Democracy)
Deliberation depends on the ability of deliberators to learn from each other through the exchange of information. However, the Common Knowledge Effect (CKE) finding, a well-established phenomenon affecting small-group discussion, shows that when people talk in groups they tend to ignore novel information and instead discuss commonly known information; things that everyone knew before discussion started. Some theorists have worried that the CKE makes small group discussion - one of the most common features of recent democratic innovations - a poor tool for making deliberative democracy a reality. However, most research on the CKE is limited to situations where group members share a common goal or interest, while political deliberation generally happens in situations where citizens have at least some conflicting interests. This paper looks for evidence of the CKE in two group-discussion experiments where subjects had partially conflicting interests, ultimately finding find no evidence of this effect. Scholars of deliberation frequently view conflicting interests as an obstacle to the success of deliberation; this result suggests that conflicting interests may, in fact, enhance deliberation by reducing the overreliance on commonly-known information.